Judicial delay, a problem of the procedural system? - Yepes Gómez, Fernando (DIXI, 2021)
Purpose: The difficulty of achieving a prompt and efficient administration of justice is not only a guarantee and a constitutional right, but also becomes an instrument to achieve peace with social justice and respect for human dignity. It is necessary to identify the reason for the saturation of the judiciary in order to propose fundamental changes, beyond the type of prevailing procedural system.Description: The judicial history in Colombia has been marked by an endemic difficulty: congestion and delay in the resolution of conflicts, added to the growing demand of the judicial apparatus that has exacerbated the weak state capacity to respond with the expected promptness. To this end, solutions have been sought based on reforms of the procedural codes that would allow greater efficiency in the work, embedding orality as the definitive component to unblock the jurisdiction. However, years later the problem has not been solved and, in fact, has become more serious.Conclusion: The desired decongestion and judicial celerity will be achieved not only with the inclusion of brief procedural schemes, eliminating unnecessary rituals and superfluous acts, regardless of the form in which it is carried out (oral, written). Improving the judge's powers of direction, investment in physical infrastructure, increasing the number of personnel in the service of the judiciary, the commitment of judicial employees and officials, and greater vigilance in their work are, among others, the means to achieve judicial decongestion.
Keywords: judicial congestion; orality; writing; reasonable time limits; administration of justice